Project management - Mohd Yazid, Abu (Penerbit Universiti Malaysia Pahang, 2018)
Outcome based Education: 1. Students are able to select a product with maximum components are 15. 2. Students are able to distinguish between project and project management based on their product. 3. Students are able to describe the potential of their project failure based on time, cost, scope and quality management. 4. Students are able to choose their product classification with justification. 5. Students are able to explain the impact of 6 factors towards their product.